2021
DOI: 10.3389/fonc.2021.778557
|View full text |Cite
|
Sign up to set email alerts
|

The Ferroptosis-Related Noncoding RNA Signature as a Novel Prognostic Biomarker in the Tumor Microenvironment, Immunotherapy, and Drug Screening of Gastric Adenocarcinoma

Abstract: BackgroundFerroptosis is a new type of cell death different from apoptosis, necrosis, autophagy, and pyroptosis. This study aimed to explore the relationship between ferroptosis-related noncoding RNA (ncRNA) and gastric adenocarcinoma with regard to immunity and prognosis.MethodsFerroptosis-related ncRNA expression profiles and clinical pathology and overall survival information were collected from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus database. The ferroptosis-related ncRNA signature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The TIDE and IPS scores exhibited differences in patients distinguished by the CRDC score, which displayed that LUAD patients with decreased CRDC risk scores had lower immune dysfunction and exclusion score as well as more possibility to benefit from immune checkpoint therapy ( Figures 7H,I ). In addition, based on the common subtype comparison analysis between two CRDC groups and melanoma samples with the information of immunotherapy reaction ( Roh et al, 2017 ; Chen et al, 2021 ), we could infer that patients with low CRDC risk were more likely to respond to anti-PD1 therapy (Bonferroni-corrected p = 0.044), yet high CRDC group may be resistant to this form of treatment (Nominal p = 0.042, Figure 7J ). In brief, we revealed that CRDC had relevance to immune characteristics, and patients with low CRDC risk exhibited greater immunocompetence than those with high risk.…”
Section: Resultsmentioning
confidence: 99%
“…The TIDE and IPS scores exhibited differences in patients distinguished by the CRDC score, which displayed that LUAD patients with decreased CRDC risk scores had lower immune dysfunction and exclusion score as well as more possibility to benefit from immune checkpoint therapy ( Figures 7H,I ). In addition, based on the common subtype comparison analysis between two CRDC groups and melanoma samples with the information of immunotherapy reaction ( Roh et al, 2017 ; Chen et al, 2021 ), we could infer that patients with low CRDC risk were more likely to respond to anti-PD1 therapy (Bonferroni-corrected p = 0.044), yet high CRDC group may be resistant to this form of treatment (Nominal p = 0.042, Figure 7J ). In brief, we revealed that CRDC had relevance to immune characteristics, and patients with low CRDC risk exhibited greater immunocompetence than those with high risk.…”
Section: Resultsmentioning
confidence: 99%
“…Immune checkpoints, negative regulators of immune activation, can downregulate the immune state of the body and limit antitumor responses ( 35 , 36 ). Tumor Immune Dysfunction and Rejection (TIDE) is a computational framework developed to assess the potential of tumor immune escape from gene-expressed cancer samples and to measure the responsiveness of immune checkpoint inhibitors ( 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, tumor cells and their surrounding microenvironment can be shaped by varying degrees of ferroptosis activation ( Zavros, 2017 ; Xiao et al, 2021 ). It has been found that ferroptosis serves as an important factor in the formation of the TME in GC ( Jiang et al, 2021b ; Wang F. et al, 2021 ; Chen et al, 2021b ). In addition, numerous studies have demonstrated that dying cells, including ferroptotic cancer cells, communicate with the immune cells in the TME via a series of signals ( Friedmann Angeli et al, 2019 ).…”
Section: Tumor Microenvironment In Gastric Cancermentioning
confidence: 99%